Aviation personnel: update of the concepts - Гусар, Ольга Анатоліївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article investigates the standards of the Air Code of Ukraine that regulate the concept and status of aviation personnel. The article analyzes their correlation with the regulations state of the Aviation Service acts of Ukraine. The author concludes that the normative fixed structure of aviation personnel missing a large group of subjects who perform with him the same type of function. This part of the personnel is proposed to be defined as «other personnel whose activities are directly related to the use of civil aviation». The unity of the functions legal nature of aviation personnel and other personnel, whose activities are directly related to the use of civil aviation, allows defining as «civil aviation personnel». On this basis, the author formulates a proposal to expediency of using in the aviation notion and the term «civil aviation personnel» instead of the notion and the term «aviation personnel».